Irisin plasma concentration in PCOS and healthy subjects is related to body fat content and android fat distribution. (2nd November 2015) - Pukajło, Katarzyna; Łaczmański, Łukasz; Kolackov, Katarzyna; Kuliczkowska-Płaksej, Justyna; Bolanowski, Marek; Milewicz, Andrzej; Daroszewski, Jacek
Abstract: Irisin (Ir), a recently identified adipo-myokine, cleaved and secreted from the protein FNDC5 in response to physical activity, has been postulated to induce the differentiation of a subset of white adipocytes into brown fat and to mediate the beneficial effects on metabolic homeostasis. Metabolic syndrome (MS), a cluster of factors leading to impaired energy homeostasis, affects a significant proportion of subjects suffering from polycystic ovary syndrome (PCOS). The aim of our study was to investigate the relationship between Ir plasma concentrations and metabolic disturbances. The study group consisted of 179 PCOS patients and a population of 122 healthy controls (both groups aged 25–35 years). A subset of 90 subjects with MS was isolated. A positive association between Ir plasma level and MS in the whole group and in controls was found. In subjects with high adipose body content (>40%), Ir was higher than in lean persons (<30%). Our results showed a significant positive association between Ir concentration and android type of adipose tissue in the whole study group and in the control group. Understanding the role of Ir in increased energy expenditure may lead to the development of new therapeutics for obesity and obesity-related diseases. Chinese abstract: 鸢尾素（Ir）, 一个新近被发现的脂肪-肌肉细胞因子，由蛋白FNDC5在体力活动时产生应答而裂解和分泌，推测其诱导白色脂肪细胞亚单位分化为棕色脂肪，并介导棕色脂肪对代谢稳态的有益作用。代谢综合征（MS），一系列因素导致能量稳态受损，影响了相当比例的多囊卵巢综合征（PCOS）患者。我们的研究旨在探讨Ir的血浆浓度与代谢紊乱间的关系。实验组包含179名PCOS患者和122名健康对照人群（两组年龄均为25-35岁）。其中90名患有MS的受试者。实验组和对照组均发现Ir血浆浓度和MS呈正相关。在体脂含量较高（＞40%）的受试者中，Ir水平在比较瘦的患者（＜30%）高。我们的结果显示实验组和对照组的Ir浓度和雄性脂肪组织呈显著正相关。了解Ir在增加能量消耗中的作用可能有助于发展肥胖和肥胖相关疾病的新的治疗方法。